ANALISIS PENURUNAN KADAR Fe (besi) AIR SUMUR GALI DENGAN PROSES AERASI, FILTRASI DAN KOMBINASINYA - NURYANTO NURYANTO (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2012)
Nudge well is one of pure water supplying tools that is used by Indonesian to fulfill their needs. Disadvantage of using nudge well standard water from soil water is contain of high Fe. This research method was decreased the Fe concentration in water, using aeration process with pump, filtration with sand filter and combination. The result shown that Fe concentration rate in well water before and after, processing could reduce Fe 1,25 mg/l (29,32%), filtration 2,42 mg/l (57,04%) and their combination is 3,65 mg/l (85,83%). This research conclusion was the effective management could applying to inhabitants in diminish Fe concentration from well at Pelabuhan Pangkalbalam was the mixture between aeration processing and filtration